The Role of Artificial Intelligence and Robotics in the Rehabilitation of Multiple Sclerosis: A Review - Molenda, Julia; Najdek, Gabriela; Banak, Kinga; Półgrabia, Kinga; Zinkowska, Klaudia; Olek, Mateusz; Bierska, Aleksandra; Mroczka, Patryk; Rakotoarison, Sara (Quality in Sport, 2026)
Background Multiple Sclerosis (MS) is a chronic auto-immune disease of the central nervous system. MS is one of the most frequent causes of neurological disability in young adults, affecting cognitive, motor, sensory, and emotional functions. Aim This review aims to point out the possible more effective new approach of MS treatment plan including rehabilitation and technology. Material and Methods A narrative literature review was conducted based on systematic reviews, meta-analyses, and experimental studies identified through searches of the PubMed and Google Scholar databases. Results The use of technology in the rehabilitation of patients with MS can minimize severe complications by improving functional performance, mobility, respiratory efficiency, and overall quality of life. Conclusions The future of MS rehabilitation will likely depend on the integration of personalized multidisciplinary care with emerging technologies aimed at maximizing functional independence, neuroplasticity, and long-term quality of life.